The Effectiveness of School Principal Leadership in Implementing the Independent Curriculum (Case Study at MIN 1 Mataram) - Aqodiah, Aqodiah; Astini, Baiq Ida; Hasanan, Niswatun (Attadib: Journal of Elementary Education, 2024)
The emergence of independent learning has shifted the educational paradigm in Indonesia, emphasizing a student-centered approach. Consequently, the responsibility for curriculum development has been delegated to schools, enabling them to tailor the curriculum to their local needs and conditions. This research aims to examine the central role of the school principal in leading the implementation of the independent curriculum at MIN 1 Mataram. Utilizing a qualitative research methodology, the study is conducted at MIN 1 Mataram, employing data collection methods including interviews, document analysis, and observations. Primary data sources encompass the school principal, educators, and other stakeholders, while secondary data sources include scholarly journals, online publications, websites, books, and various academic literature. Data analysis follows a systematic approach involving data reduction, presentation, and verification or drawing conclusions. Ensuring the validity of the findings entails assessing internal validity (credibility), external validity (transferability), reliability (dependability), and objectivity (confirmability). Observation findings reveal several challenges, including limited teacher competencies related to the independent curriculum, suboptimal implementation of differentiated learning strategies, and incomplete integration of information technology into various activities, particularly learning processes. In addressing these challenges, the Head of MIN 1 Mataram assumes a multifaceted leadership role encompassing planning, organizing, implementing, and evaluating the independent learning initiatives within the educational unit.